Perancangan Prototipe Sistem Kontrol Catu Daya Listrik dari PLN dan Generator Berbasis Arduino Uno - Novi Yanto; Peby Wahyu Purnawan (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
This research is designed as a control system for electricity supply from PLN and a generator prototype based on Arduino. This control system functions when there is interference with the main power source and uses a generator prototype as a backup. When the PLN off there will be a sensor or relay to activate the generator prototype, so that the it starts tu running, and then need to stabilized the voltage and frequency first, before it is used as a backup source of electricity. The systems consist of ATS-AMF Panel with materials are contactor, relay, pilot lamp, push button, selector switch, Arduino, ATMega8 IC Module and a generator simulation. The voltage and frequency values from the test results are on average close to 220 Volt and 50 Hertz. From the test result, it was found that there was a time difference from starting the generator prototype when the PLN went out with what had been arranged on the ladder diagram. It takes an average of 2.64 Seconds for starting genset prototype, and it take 4.73 more seconds for the generator prototype to activate the ATS function and supply electrical power to the load. When the main source PLN is back, it takes on average 13.22 seconds for the generator prototype to cooling down before off and to process of moving the main breaker from backup supply to main source PLN. Keywords: AMF, ATS, Arduino Uno, Genset Prototype, ATMega8